PENGARUH DUKUNGAN SOSIAL ORANG TERDEKAT DALAM MEMINIMALISIR PERISTIWA DAN DAMPAK POSTPARTUM PADA IBU USIA MUDA (LITERATUR REVIEW) - Indrawati Aris Tyarini; Dewi Candra Resmi (Jurnal Ilmiah Kesehatan, 2020)
Purpose : To determine the effect of social support for those closest to minimizing events and the impact of postpartum on young mothers Methods : The methodology used the literature review in scientific publications in 2009-2018 Result : There were four journals with the same criteria showed that social support was very influential in minimizing the occurrence of postpartum and reduced the impact. Conclusion : There are two strategies in handling postpartum blues using problem & emotion focus. The strategy effectived if the individual understands and tries to improved the situation. Key Word : postpartum blues, baby blues, family social support